Therapeutic use of Red Blood Cells and Platelets Derived from Human Cord Blood Stem Cells. (1st November 2021) - Xie, Xiaoyan; Yao, Hailei; Han, Xiaoyan; Yue, Wen; Pei, Xuetao
Abstract: Red blood cells (RBCs) and platelets derived from stem cells are possible solutions to the increasing demand for blood transfusion. Based on the availability of stem cells, their relatively defined differentiation mechanisms, and the massive exploration of induction systems, the generation of RBCs or platelets in vitro from cord blood hematopoietic stem/progenitor cells (CB-HSPCs) has potential for clinical applications. However, information on the clinical translation of stem cell-derived RBCs and platelets in the literature and at the ClinicalTrials.gov website is very limited. The only clinical trial on cultured RBCs, which aimed to assess the lifespan of RBCs cultured in vivo, was reported by Luc Douay and colleagues. Of note, the cultured RBCs they used were derived from autologous peripheral blood HSPCs, and no cultured platelets have been applied clinically to date. However, CB-HSPC-derived megakaryocytes, platelet precursors, have been used in the treatment of thrombocytopenia. A successful phase I trial was reported, followed by phase II and III clinical trials conducted in China. In this review, the gap between the many basic studies and limited clinical trials on stem cell-derived RBCs and platelets is summarized. The possible reasons and solutions for this gap are discussed. Further technological improvements for blood cell expansion and maturation ex vivo and the establishment of biological standards for stem cell derivatives might help to facilitate the therapeutic applications of cultured RBCs and platelets derived from CB-HSPCs in the near future. Abstract : We review the progress in producing red blood cells (RBCs) and platelets from human cord blood hematopoietic stem/progenitor cells (HSPCs) and relatively limited reports on the clinical trials with cultured RBCs and megakaryocytic progenitors (MPs). Technical improvement together with the establishment of biological standards for stem cell derivations might help to achieve therapeutic applications of cultured RBCs and platelets. EPCs, erythroid progenitor cells.